2019
DOI: 10.1128/jcm.01417-18
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of a Rapid Immunochromatographic Assay for Detection of PBP2a in Non-Staphylococcus aureus Staphylococcal Species

Abstract: Non-Staphylococcus aureus staphylococcal species (non-SASS) are important pathogens in both animal and human populations. The development of ␤-lactam resistance in non-SASS through acquisition and expression of penicillin-binding protein 2a (PBP2a) represents a significant clinical and public health threat. Here, we evaluated the diagnostic performance of two versions of a PBP2a immunochromatographic assay with non-SASS. Our data show that the revised version of the assay, the PBP2a SA culture colony test, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The PBP2a SA culture colony test, which is approved by the FDA for PBP2a detection in S. aureus, was 100% sensitive and 100% specific for S. epidermidis isolates by the use of the default manufacturer instructions (i.e., without oxacillin induction). These findings are consistent with other studies that reported 100% sensitivity and specificity for other staphylococcal species, including 50 S. epidermidis (11) and 54 S. schleiferi (8) isolates. Although the PBP2= latex agglutination test kit is FDA approved for both S. aureus and CoNS (with oxacillin induction), two false negatives were identified, resulting in overall sensitivity and specificity of 95.8% and 100%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The PBP2a SA culture colony test, which is approved by the FDA for PBP2a detection in S. aureus, was 100% sensitive and 100% specific for S. epidermidis isolates by the use of the default manufacturer instructions (i.e., without oxacillin induction). These findings are consistent with other studies that reported 100% sensitivity and specificity for other staphylococcal species, including 50 S. epidermidis (11) and 54 S. schleiferi (8) isolates. Although the PBP2= latex agglutination test kit is FDA approved for both S. aureus and CoNS (with oxacillin induction), two false negatives were identified, resulting in overall sensitivity and specificity of 95.8% and 100%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, the red lines observed with methicillin-resistant SNA isolates were often less intense than those observed with MRSA isolates, indicating that the operator must strictly respect the inoculum recommendations of the manufacturer (one heaped 1-l bacteriological loop of colonies) to avoid false-negative results. The high sensitivity for mecA-positive isolates is concordant with the results obtained with the previous version for S. aureus isolates (2)(3)(4)9), and our study confirmed, using a large collection of species and isolates, that the performance of this revised assay was largely improved for SNA species, as reported by Canver et al (6). Conversely, unlike with the previous version of the assay, no improvement in the detection of mecCpositive MRSA isolates was observed with cefoxitin induction, indicating that the antibodies and/or protocol used in the revised assay no longer allow the detection of PBP2c.…”
supporting
confidence: 92%
“…ELISAs eliminate sophisticated sample pretreatment and can tolerate certain matrix interferences because of washes between steps. Compared with ELISAs, immunochromatographic lateral flow strip test (ILFST) is simpler and rapid immunoassay that has been used in detecting pesticides (Byzova, Urusov, Zherdev, & Dzantiev, 2018;Ismail et al, 2016), veterinary drugs (Chen et al, 2017;Shelver & Smith, 2018), mycotoxins (Di Nardo et al, 2019;Majdinasab, Zareian, Zhang, & Li, 2019), bacteria (Canver et al, 2019;Saleh, Göttig, & Hamprecht, 2018), and viruses (Lyoo et al, 2017;Senthilkumaran et al, 2017). ILFST integrates all the required reagents into itself and can provide the results within 10 min that can be determined both qualitatively and quantitatively with unaided eyes and a strip reader, respectively.…”
Section: Introductionmentioning
confidence: 99%